Effect of commercial nasal steroid preparation on bacterial growth. Issue 7 (12th February 2019) - Cherian, Lisa Mary; Cooksley, Clare; Richter, Katharina; Ramezanpour, Mahnaz; Paramasivan, Sathish; Wormald, Peter‐John; Vreugde, Sarah; Psaltis, Alkis James
Abstract : Background: Topical budesonide (Pulmicort; AstraZeneca AB, Sodertalje, Sweden) is commonly used in the management of chronic rhinosinusitis (CRS). Although its use is due to its perceived anti‐inflammatory effect, studies have suggested that it may also have antibacterial properties. To make the hydrophobic steroid molecule suitable for topical administration, pharmaceutical excipients are used in commercial steroid formulations. Herein we investigated the antibacterial action of commercial budesonide and its excipients. Methods: Planktonic and biofilm forms of Staphylococcus aureus and methicillin‐resistant Staphylococcus aureus (MRSA) were treated with Pulmicort or its excipients at clinically relevant concentrations. Bacterial growth was determined by optical density, resazurin assays, colony‐forming unit counts, and Giemsa staining. Minimum inhibitory concentration (MIC) studies assessed excipients' potentiation of antibiotics. Experiments were conducted in triplicate and results analyzed using one‐way analysis of variance. Results: There was significant reduction in planktonic and biofilm growth of S aureus and MRSA on exposure to budesonide ( p < 0.0001) and its excipients ( p < 0.0001). Excipient ethylene diamine‐tetraactic acid (EDTA) demonstrated an antibacterial property even at the low concentrations used in topical preparations ( p < 0.0001). With amoxicillin, excipients exhibited a potential additive/synergistic effect on MIC, whereas erythromycin and aminoglycosides showed an antagonistic action. Conclusion: The commercial product Pulmicort has a direct antibacterial effect on the planktonic and biofilm forms of S aureus and MRSA. This effect is at least in part mediated through the excipient EDTA in the product. Excipients also influenced the antimicrobial activity of antibiotics depending on the bacterial strain and antibiotic tested.